Assessing energy poverty alleviation, energy security enhancement, and decent work and economic growth in China under SDGs 7 and 8: A meta parallel two-stage dynamic SBM-DEA analysis - Li Ji; Yung-ho Chiu; Tzu-Han Chang; Li Yang; Hsiang-Yue Chen (Journal of Cleaner Production, 2026)

Integrated Multi-Endpoint Analysis of Soluble Copper(II) Chloride–Induced Oxidative Stress, Mitochondrial Dysfunction, and Genotoxicity in RAW264.7 Macrophages - Ping-Kun Tsai; Sheng-Wen Wu; Yen-Ju Lee; Yu-Ting Chang; Shiuan-Shinn Lee; Yung-Chuan Ho; Li-Chiu Yang; Yu-Hsiang Kuan (Biological Trace Element Research, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Physicochemical modulation of soy-hemp-wheat protein meat analogues prepared by high-moisture extrusion using transglutaminase - Zhouliang Sun; Wanhui Zhang; Fengkai Zhang; Ivy Chiu; Dan Li; Xinghui Wu; Tianxi Yang; Yang Gao; Huanyu Zheng (Food Research International, 2025)

Mechanistic insights into curdlan-induced fibrous structure formation in soybean protein and wheat gluten extrudates via dead-stop operation and rheological characterization - Kaili Zhang; Dan Li; Ivy Chiu; Xiaohang Guo; Zhouliang Sun; Xinghui Wu; Danyi Liu; Hao Chen; Tianxi Yang; Yang Gao; Huanyu Zheng (Food Hydrocolloids, 2025)

Flood resilience through hybrid deep learning: Advanced forecasting for Taipei's urban drainage system - Li-Chiu Chang; Ming-Ting Yang; Fi-John Chang (Journal of Environmental Management, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

The dominance of K-strategy microbes enhances the potential of soil carbon decomposition under long-term warming - Yanli Gao; Jiacong Zhou; Teng-chiu Lin; Yiqing Li; Quanxin Zeng; Shidong Chen; Decheng Xiong; Qiufang Zhang; Zhijie Yang; Yusheng Yang (Applied Soil Ecology, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Epidemiology of human metapneumovirus in Taiwan from 2013 to 2023 - Su-Lin Yang; Tai-Yuan Chiu; Kun-Lin Tsai; Chung-Hao Li; Jyh-Yuan Yang; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Microfluidics enhanced biosensor technology for advancing food safety monitoring - Guangfu Wu; Huijie Li; Jialong Chen; King Wai Chiu Lai; Lize Xiong; Runhuai Yang (Trends in Food Science & Technology, 2024)

Advancing climate-resilient flood mitigation: Utilizing transformer-LSTM for water level forecasting at pumping stations - Pu-Yun Kow; Jia-Yi Liou; Ming-Ting Yang; Meng-Hsin Lee; Li-Chiu Chang; Fi-John Chang (Science of The Total Environment, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Effects of benzophenone-3 and its metabolites on the marine diatom Chaetoceros neogracilis: Underlying mechanisms and environmental implications - Yi Yang; Guang-Jie Zhou; Ziying Li; Jiaji Sun; Alice Sze Tsai Wong; Vincent Chi Chiu Ko; Rudolf Shiu Sun Wu; Keng Po Lai (Science of The Total Environment, 2024)

Reassessment of industrial eco-efficiency in China under the sustainable development goals: A meta two-stage parallel entropy dynamic DDF-DEA model - Li Yang; Shiying Chen; Yung-ho Chiu; Tzu-Han Chang; Yue Wang (Journal of Cleaner Production, 2024)

Reassessment of the efficiency of China's industrial circular economy considering quality of life: a meta recycle SBM dynamic under exogenous model - Anqi Lei; Li Yang; Yung-ho Chiu; Yuan-yuan Niu; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

In vitro and in vivo anti-tumor activity of Coenzyme Q0 against TWIST1-overexpressing HNSCC cells: ROS-mediated inhibition of EMT/metastasis and autophagy/apoptosis induction - Hsin-Ling Yang; Li-Wen Chiu; Yi-An Lin; Sudhir Pandey; Chithravel Vadivalagan; Jiunn-Wang Liao; Yugandhar Vudhya Gowrisankar; Hui-Jye Chen; Hui-Yi Lin; You-Cheng Hseu (Toxicology and Applied Pharmacology, 2023)

Porous electrodes from self-assembled 3D jointed Pd polyhedra for direct formic acid fuel cells - Yang Li; Yichang Yan; Ming-Shui Yao; Feng Wang; Yanhong Li; Sean M. Collins; Yu-Lung Chiu; Shangfeng Du (Chemical Engineering Journal, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Root litter inputs exert greater influence over soil C than does aboveground litter in a subtropical natural forest - Xiaofei Liu; Teng-Chiu Lin; Matthew A. Vadeboncoeur; Zhijie Yang; Shidong Chen; Decheng Xiong; Chao Xu; Yiqing Li; Yusheng Yang (Plant and Soil, 2019)

Increased litter in subtropical forests boosts soil respiration in natural forests but not plantations of Castanopsis carlesii - Xiaofei Liu; Teng-Chiu Lin; Zhijie Yang; Matthew A. Vadeboncoeur; Chengfang Lin; Decheng Xiong; Weisheng Lin; Guangshui Chen; Jinsheng Xie; Yiqing Li; Yusheng Yang (Plant and Soil, 2017)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Structure and function of subterranean gallery systems of soil-feeding termites Pericapritermes nitobei and Sinocapritermes mushae - C.-I. Chiu; M.-M. Yang; H.-F. Li (Insectes Sociaux, 2015)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Vibrational analysis of mandible trauma: experimental and numerical approaches - Shu-Li Lin; Sheng-Yang Lee; Long-Yi Lee; Wen-Ta Chiu; Che-Tong Lin; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2006)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)